Musik Kontemporer Sebagai Media Memperkenalkan Nilai-Nilai Agama Hindu Di Daerah Khusus Ibukota Jakarta - Prameswara, Indra; Suhardi, Untung; Awiyane, Wayan Tantre (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2018)
This thesis discusses Contemporary Music as a Media Introducing Hindu Religious Values in DKI Jakarta. The purpose of this research is to find out how the lyrics of contemporary music as a media introduce Hindu religious values in DKI Jakarta and to find out how Hindu views towards contemporary music lyrics as a media introducing Hindu religious values in DKI Jakarta. This research si qualitative research with descriptive design. Data collection techniques using interviews, observation, and documentation. The author conducted interviews with informants, the author collected data about 4 months in the field. The results of the study prove that contemporary music lyrics can be used as a medium in introducing Hindu religious values in DKI Jakarta. By using genres, and themes in making lyrics packed with contemporary music. So that it can provide a good view for Hindus in DKI Jakarta in recognizing Hindu religious values which are arranged in song lyrics from Dewa Budjana, Novi Surya and Alam Dewata Band. So that Hindus are expected to be able to recognize the values of Hinduism to be used as a guide in carrying out life.